The Influence of Lifestyle and Financial Literacy on the Use of Fintech Payments Paylater Among Students of the Faculty of Economics, Prima Indonesia University in Medan: engaruh Gaya Hidup dan Literasi Keuangan Terhadap Penggunaan Fintech Pembayaran Paylater di Kalangan Mahasiswa Fakultas Ekonomi Universitas Prima Indonesia Medan - Rivaldo Rivaldo; Afrizal; Melissa Mangali; Earvin John Medina (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
The rising adoption of financial technology, especially payment options like